Modified Delphi Procedure to Achieve Consensus for the Concept of a National Curriculum for Minimally Invasive and Robot-assisted Surgery in Germany (GeRMIQ) Modifiziertes Delphi-Verfahren zur Konsensfindung für die Konzeption eines bundesweiten Curriculums für minimalinvasive und roboterassistierte Chirurgie in Deutschland (GeRMIQ) - Huber, Tobias; Weber, Julia; Von Bechtolsheim, Felix; Flemming, Sven; Fuchs, Hans Friedrich; Grade, Marian; Hummel, Richard; Krautz, Christian; Stockheim, Jessica; Thomaschewski, Michael; Wilhelm, Dirk; Kalff, Jörg C.; et al. (Zentralblatt für Chirurgie, 2024)
Background The rapid development of minimally invasive surgery (MIS) and robot-assisted surgery (RAS) requires standardized training to ensure high-quality patient care. In Germany, there is currently a lack of a standardized curriculum that teaches these specialized skills. The aim of this study is to find a consensus for the development of a nationwide curriculum for MIS and RAS with the subsequent implementation of the consented content. Methods A modified Delphi process was used to reach consensus among national experts in MIS and RAS. The process included a literature review, an online survey and an expert conference. Results All 12 invited experts participated in the survey. They primarily achieved consensus on 73% and secondarily within the expert conference on 95 out of 122 questions (77.9 %). The preference for a basic curriculum as a foundation on which specialized modules can build on was particularly clear. The results support the development of an integrated curriculum for MIS and RAS that includes step-by-step training from theoretical knowledge via e-learning modules to practical skills in dry lab simulations and in the OR. Emphasis was placed on the need to promote clinical judgment and decision making through targeted assessment during the learning curve to ensure effective application of learned skills in clinical practice. There was also a consensus that training content must be aligned with learners' skill acquisition using objective performance assessments in line with the principle of proficiency-based progression (PBP). The continuous updating of the curriculum to keep it up to date with the latest technology was considered essential. Conclusion The study underlines the urgent need for a standardized training curriculum for MIS and RAS in Germany in order to increase patient safety and improve the quality of surgical care. There is broad expert consensus for the implementation of such a curriculum. It aims to ensure a contemporary and internationally competitive uniform quality of training and to increase the attractiveness of surgical training.
CRIS-Team Scopus Importer:2025-02-04
Keywords: consensus; curriculum; Delphi process; minimally invasive surgery; robot-assisted surgery